INCIDENCE OF CATARACT IN DOGS : A RETROSPECTIVE STUDY - C. Ramani; Manoj Kumar Ahirwar; Mohd. Shafiuzama; Nitin J D’souza; L. Nagarajan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Retrospective data on the incidence of status of cataract were obtained for a period of two years from October 2009 to September 2011 after scrutinizing the hospital record at ophthalmology unit, Department of Veterinary Surgery and Radiology, Madras Veterinary College Teaching Hospital. A higher incidence of cataract was observed in the breed Spitz aged between 7-15 years